2008
DOI: 10.1242/dev.019125
|View full text |Cite
|
Sign up to set email alerts
|

Induction of mirror-image supernumerary jaws in chicken mandibular mesenchyme by Sonic Hedgehog-producing cells

Abstract: Previous studies have shown that Sonic Hedgehog (Shh) signaling is crucial for the development of the first branchial arch (BA1) into a lower-jaw in avian and mammalian embryos. We have already shown that if Shhexpression is precociously inhibited in pharyngeal endoderm, neural crest cells migrate to BA1 but fail to survive, and Meckel's cartilage and associated structures do not develop. This phenotype can be rescued by addition of an exogenous source of Shh. To decipher the role of Shh, we explored the conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 59 publications
3
56
1
Order By: Relevance
“…Previously, sonic hedgehog (Shh) has been shown to regulate growth and proliferation of the mandibular arch (Brito et al, 2008;Roper et al, 2009;ten Berge et al, 2001). We have observed that Shh is expressed in similar domains in duck and quail embryos (Fig.…”
Section: Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, sonic hedgehog (Shh) has been shown to regulate growth and proliferation of the mandibular arch (Brito et al, 2008;Roper et al, 2009;ten Berge et al, 2001). We have observed that Shh is expressed in similar domains in duck and quail embryos (Fig.…”
Section: Developmentmentioning
confidence: 99%
“…Shh expression in the pharyngeal endoderm is essential for mandibular development, where it directs neural crest survival and outgrowth (Ahlgren and Bronner-Fraser, 1999;Balczerski et al, 2012;Brito et al, 2006;Brito et al, 2008;David et al, 2002;Jeong et al, 2004;Veitch et al, 1999). Exogenous Shh, when placed in the mandibular arch environment, activates Bmp4 and Fgf8 expression in the oral ectoderm, resulting in the development of supernumerary mandibles (Brito et al, 2008). Together, these data support the hypothesis that jaw size is reliant on proliferation within the mandibular arch environment (regulative development) rather than being entirely dependent on initial NC progenitor number (determinant development).…”
Section: Regulative Development Of the Mandiblementioning
confidence: 99%
“…The first arch, the mandibular arch, is an exception as it is devoid of Hox gene expression (Rijli et al, 1998;Pasqualetti et al, 2000;Trainor and Krumlauf, 2000;Baltzinger et al, 2005). In addition, signals from the endoderm and the ectoderm, which overlie the branchial arches, are crucial for correct craniofacial development and for the specification of the first branchial arch (Couly et al, 2002;Miller et al, 2003;Brito et al, 2008;Nair et al, 2007;Sato et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The migration routes as determined in DiI (1,1 0 , di-octadecyl-3,3,3 0 ,3 0 ,-tetramethylindocarbocyanine perchlorate) labeling studies show that cells entering the midline of upper face will pass by the eyes and forebrain (Lumsden et al, 1991). Although both the frontonasal neural crest cells as well as those destined for the mandibular arch are influenced by signals coming from the pharyngeal endoderm such as sonic hedgehog (Brito et al, 2006(Brito et al, , 2008Benouaiche et al, 2008), ultimately with expansion of the brain the frontonasal mass is more dependent on signals from the forebrain than the endoderm (Hu and Marcucio, 2009) and as such the same signals could also serve to distinguish the gene expression profile of the frontonasal mass. In addition, our results are perhaps biased as a result of the stage chosen for the expression profiling.…”
Section: Resultsmentioning
confidence: 99%